2021
DOI: 10.3389/fimmu.2020.628804
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Long-Term Protective Immunity Induced by Vaccination With Mycoplasma gallisepticum Strain ts-304

Abstract: Live attenuated vaccines are commonly used to control Mycoplasma gallisepticum infections in chickens. M. gallisepticum ts-304 is a novel live attenuated vaccine strain that has been shown to be safe and effective. In this study, the transcriptional profiles of genes in the tracheal mucosa in chickens challenged with the M. gallisepticum wild-type strain Ap3AS at 57 weeks after vaccination with ts-304 were explored and compared with the profiles of unvaccinated chickens that had been challenged with strain Ap3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
0
4
2
Order By: Relevance
“…Therefore, the earlier recruitment of B cells seen in the current study in the tracheal mucosa of mature birds contrasts with previous studies on young birds (Gaunson et al, 2000(Gaunson et al, , 2006b, providing further evidence for age-related differences in the severity of M. gallisepticum induced immune dysregulation (Kulappu Arachchige et al, 2020;Kulappu Arachchige et al, 2021). In addition, there was no significant difference in the transcription of genes encoding key proinflammatory cytokines, including IL-1β and IL-6, in the tracheal mucosa of chickens infected after 40 weeks of age in this study as well as in a previous study investigating the genome-wide transcriptional profiles in the tracheas of the same chickens challenged with virulent M. gallisepticum at 57 weeks after vaccination (Kulappu Arachchige et al, 2021). This is in contrast to previous observations in chickens infected at a younger age (Gaunson et al, 2000(Gaunson et al, , 2006bKulappu Arachchige et al, 2020;Mohammed et al, 2007).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Therefore, the earlier recruitment of B cells seen in the current study in the tracheal mucosa of mature birds contrasts with previous studies on young birds (Gaunson et al, 2000(Gaunson et al, , 2006b, providing further evidence for age-related differences in the severity of M. gallisepticum induced immune dysregulation (Kulappu Arachchige et al, 2020;Kulappu Arachchige et al, 2021). In addition, there was no significant difference in the transcription of genes encoding key proinflammatory cytokines, including IL-1β and IL-6, in the tracheal mucosa of chickens infected after 40 weeks of age in this study as well as in a previous study investigating the genome-wide transcriptional profiles in the tracheas of the same chickens challenged with virulent M. gallisepticum at 57 weeks after vaccination (Kulappu Arachchige et al, 2021). This is in contrast to previous observations in chickens infected at a younger age (Gaunson et al, 2000(Gaunson et al, , 2006bKulappu Arachchige et al, 2020;Mohammed et al, 2007).…”
Section: Discussioncontrasting
confidence: 96%
“…We chose a panel of 13 cytokines and chemokines mediating different types of immune responses based on previous publications that investigated the levels of transcription of cytokine and chemokine genes in chickens after infection with several pathogens, including M. gallisepticum, Eimeria species and Salmonella species (Hong, Lillehoj, Lee, Dalloul, & Lillehoj, 2006;Mohammed et al, 2007;Withanage et al, 2004), with the aim of gaining insights into the different types of immune responses prevailing at 2 weeks after infection with M. gallisepticum. Of these 13 cytokine and chemokine genes, only those for IFN-γ and MIP-1β were found to be differentially transcribed in our previous study investigating global transcriptional profiles in three randomly chosen chickens from each group at 57 weeks after vaccination (Kulappu Arachchige et al, 2021). In contrast, in the current study we observed differential transcription of the genes for IFN-γ, CXCL-14, RANTES, IL-2, IL-6 and IL-17, but no significant differences in transcription of the gene for MIP-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, it also has been effective but at a lower dose and protective against challenge with the MG wild-type strain. In addition, its protection lasts for at least 57 weeks after a single vaccination at 3 weeks of age (Kulappu Arachchige et al, 2021). Since live vaccines are used in many parts of the world, Sulyok and his team have developed new highly specific molecular methods to rapidly differentiate MG vaccine strains from field virulent isolates using clinical samples (Sulyok et al, 2019).…”
Section: Avian Infectionmentioning
confidence: 99%
“…MG mainly infects turkeys and chickens, but it has also been reported in other birds ( Sawicka et al, 2020 ); it can be transmitted horizontally through direct or indirect contact or vertically through eggs ( Kleven, 2008 ). Although vaccination is effective for MG at present ( Bennett et al, 2013 ; Condello et al, 2020 ; Arachchige et al, 2021 ), vaccination against MG is not prevalent due to the variation of bacterial strains and the lack of means to prevent horizontal infection ( Feberwee et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%